ASSOCIATION OF SERUM VITAMIN D LEVELS WITH SYSTEMIC LUPUS ERYTHEMATOSUS PATIENTS- A CASE CONTROL STUDY FROM TERTIARY CARE HOSPITAL. - MEERA ANN JOHN; Rajarshri Bhowal; Biswadeep Choudhury; Joydeep Roy; Simi Patoa; Vandana Pradhan; Nivedita Dasgupta (Student's Journal of Health Research Africa, 2024)
Background- The Vitamin D deficiency prevalence is increasing and has been linked to numerous chronic and autoimmune conditions. This research aims to establish the relationship among Vitamin D and SLE (Systemic Lupus Erythematosus). Methodology- A case-control research has been conducted on 42 confirmed SLE patients at the Department of Dermatology and the Department of Medicine at Silchar Medical College and Hospital, along with 50 healthy controls matched for age and gender. All samples underwent immunofluorescence testing for dsDNA, ANCA, ANA, and radioimmunoassay for levels of Vitamin-D. Results- The average Vitamin-D levels in the SLE cases group have been calculated to be 17.57 with a SD (Standard Deviation) of 4.51. The control group had a mean of 52.23 and an SD of 2.01. A paired test comparing Vitamin-D levels in the cases of SLE as well as control groups showed a p-value of <0.001, indicating statistical significance. Following supplementation of Vitamin-D, the average in the SLE cases group had been 46.82, with an SD of 14.65. A paired sample t-test has been conducted on the data collected before as well as after Vitamin D supplementation in the SLE cases group, giving a p-value of <0.001, indicating statistical significance. There has been no statistically major relation between the various ANA types, with p-values of 0.09 following supplementation and 0.21 prior to it. As a result, statistical insignificance was concluded. Conclusion- SLE patients have lower levels of Vitamin-D than the healthy individuals. Vitamin-D did not display a major correlation with the different patterns of ANA in patients of SLE. Keywords: Vitamin D, SLE, Immune responses.